2007
DOI: 10.1073/pnas.0608382104
|View full text |Cite
|
Sign up to set email alerts
|

Acute postnatal ablation of Hif-2 α results in anemia

Abstract: Adaptive transcriptional responses to oxygen deprivation (hypoxia) are mediated by the hypoxia-inducible factors (HIFs), heterodimeric transcription factors composed of two basic helix-loop-helix-PAS family proteins. The transcriptional activity of HIF is determined by the hypoxic stabilization of the HIF-␣ proteins. HIF-1␣ and HIF-2␣ exhibit high sequence homology but have different mRNA expression patterns; HIF-1␣ is expressed ubiquitously whereas HIF-2␣ expression is more restricted to certain tissues, e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
369
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(387 citation statements)
references
References 38 publications
12
369
2
4
Order By: Relevance
“…[85][86][87][88] Recent reports suggest that another HIF family member, HIF-2, is the major inducer of EPO in hypoxia. 39,89 Not only does EPO production by astrocytes have local effects, but ablation of HIF-2 function selectively in astrocytes causes anemia during hypoxia-ischemia, demonstrating the importance of astrocyte EPO production for erythropoiesis. 90 Several studies suggest a neuroprotective role for EPO (FIG.…”
Section: Astrocytes and Epo As A Neuroprotectantmentioning
confidence: 99%
“…[85][86][87][88] Recent reports suggest that another HIF family member, HIF-2, is the major inducer of EPO in hypoxia. 39,89 Not only does EPO production by astrocytes have local effects, but ablation of HIF-2 function selectively in astrocytes causes anemia during hypoxia-ischemia, demonstrating the importance of astrocyte EPO production for erythropoiesis. 90 Several studies suggest a neuroprotective role for EPO (FIG.…”
Section: Astrocytes and Epo As A Neuroprotectantmentioning
confidence: 99%
“…Recent analysis of HIF-2α knockdown mice revealed that EPO gene expression was significantly affected, in parallel with HIF-2α expression [12]. Conditional knockout of HIF-2α after birth demonstrated that HIF-2α plays a critical role in adult erythropoiesis [13]. In addition, studies using mice with conditional knockout of HIF-1α and/or HIF-2α in hepatocytes revealed that the hypoxic induction of liver EPO in anemic mice was also HIF-2α dependent [14].…”
Section: Mechanisms Of Renal Erythropoietin Productionmentioning
confidence: 99%
“…[42][43][44][45][46][47] At the molecular level, several HIF-2a preferentially regulated genes have been identified, including CCND1, EPO, POU5F1, TGFA, and VEGFA (encoding cyclin D1, erythropoietin, octamer-binding transcription factor 4, transforming growth factor a, vascular endothelial growth factor A, respectively). 46,48,49 However, how HIF-2a specifically targets these genes remains unclear, although the involvement of ETS transcription factors in HIF-2a target gene selection has been suggested.…”
Section: Hif-2a In Contrast With Hif-1a Promotes Cell Proliferationmentioning
confidence: 99%